Assesment of genetic diversity of seeding for shorea dyer ex king using damd markers - Roznah, Abdul Jabbar. (Universiti Malaysia Sarawak (UNIMAS), 2004)
The assessment of the genetic diversity of seedlings for Shorea curtisii Dyer ex King was successfully determined by using DAMD markers. 30 DNA samples, each from before and after logging, which was collected from Compartment 118, Ulu Sed iii Forest Reserve, lohor, were used in this study. The Shannon diversity Index and percentage of polymorphic loci were used to quantify the genetic diversity changes of seedlings based on 26, 25 and 24 reproducible fragments or DAMD loci generated by primers M13, 33.6 and YNZ-2, respectively. Results from the present study showed a significant reduction of genetic diversity in seedlings after a single selective logging event under Selective Management System (SMS). The reduction of Shannon diversity Index in seedling was 23.1% after logging i.e. from 0.304 to 0.234. Therefore, the primers M13, 33.6 and YNZ2 are sensitive in monitoring genetic diversity changes or genetic erosion resulting from logging.